Impact of technological progress in the treatment of lithiasis residual common bile duct - Aizen, Bernardo (Cirugía del Uruguay, 1995)
The authors describe new therapeutical options in the treatment of residual lithiasis of the choledochus as regards indicatíons, results and morbimortality; the place of biliar re-operatíon surgery is a/so defined. Based on this, a therapeutical plan is proposed, and the influence of technological advances in the management of this disease in reference centers and among us is a/so analysed.